Evaluating the No Zero Grading Technique (NZGT) as a Veritable Tool for Enhancing Students’ Interest and Achievement in Mathematics in an Ubuntulised Classroom - Terungwa James Age; Masilo France Machaba (E-Journal of Humanities, Arts and Social Sciences)
The persistent challenge of student interest and achievement in mathematics has led educators to explore innovative teaching and assessment approaches. This experimental study investigated the impact of integrating the No Zero Grading Technique (NZGT) within an Ubuntu classroom environment on students’ interest and achievement in mathematics. The study employed a quasi-experimental, control group pretest-posttest design involving 165 Upper Basic II students from two public secondary schools in Benue State, Nigeria. The Mathematics Interest Questionnaire (MIQ) and Mathematics Achievement Test (MAT) were used to collect data. The experimental group received the NZGT intervention within an Ubuntu classroom setting for 12 weeks, while the control group maintained traditional grading practices in a similar Ubuntu environment. Analysis of Covariance (ANCOVA) revealed significant differences in both interest levels (F = 14.953, p < .05, partial η² = .085) and achievement scores (F = 16.162, p < .05, partial η² = .091) favoring the experimental group. These findings suggest that the integration of NZGT within an Ubuntu classroom can significantly enhance both student interest and achievement in mathematics. The study contributes to the growing body of literature on alternative assessment practices and culturally responsive pedagogies in mathematics education, offering promising strategies for improving mathematics instruction and addressing longstanding challenges in the field.